HISTORICAL BACKGROUND AND BARRIERS FOR ECONOMIC COOPERATION ON THE EXAMPLE OF JAPAN AND SOUTH KOREA - Shatskykh , R.D.; Rodionova , T.A. (The actual problems of regional economy development, 2023)
This article aims to study the significance that historical events play in the development of current international relations and economic relations between two countries. The countries used in the article are Japan and South Korea. Those countries represent a difficult case of past historical hardships. Data from both before and after the World War 2 is used to show the long history these countries share. During the analysis, the exact degree of damage to the relations between these two countries is determined. The article proceeds to show the positive advances which two countries initiate. Based on the current information and historical statistical data, it is concluded that two countries continue their political economic and even military cooperation despite the hardships they faced in the past. Japan and South Korea also take active part in investing in each other’s economies which further shows the degree of cooperation in economic aspect. The regression model constructed in the article only further supports the claim that two countries were able to overcome the issues of the past and move on to have a productive and efficient relations in the present. The scientific and practical value of this work is that many other countries can get valuable information about cooperation and recovery. For Ukraine, this work can be valuable in two ways. The experience of these countries in post-war reconstruction and development, as well as their cooperation despite historical problems. For Ukraine in particular, after the end of hostilities, a window of opportunity opens, similar to what happened to Japan and South Korea at the beginning of their journey. With sufficient material and technological assistance from the USA and European countries, Ukraine can try to repeat the experience of Japan or South Korea. But at the same time, the country must be careful not to make mistakes made in the past. Given the characteristic features of the economy, circumstances, and historical experience, it is even possible to surpass the results achieved by Japan and South Korea. The second point is close cooperation with Western neighbors. For the Ukraine of the future, it is very important to preserve these friendly relations and further develop them. As experience shows, cooperation always brings positive results for both parties, bringing them closer to the main goal - economic growth and well-being. In the course of writing the article, the following research methods were used: analysis of literature and statistical data on the research topic, induction and deduction, modeling, generalization and synthesis of the obtained information.